Anchored Montmorillonite Diphenyl Phosphino Palladium(II) Chloride Mediated Hydrogenation of Maleic Anhydride and Its Related Geometric Isomers: A Kinetic Study - Hemasri, Y.; Jaya Prakash Rao, Y.; Rajanna, K.C.; Saiprakash, P.K. (Asian Journal of Chemistry, 2010)
A kinetic study of hydrogenation of maleic anhydride and few related geometrical isomers has been carried out with anchored montmorillonite diphenyl phosphino palladium(II) chloride as the catalyst in the temperature range of 288-306 K. Reaction kinetics indicated first order dependence on [H2]. A mechanism consistent with the experimental data has been proposed. The activation and thermodynamic parameters have been evaluated.